Analysis Streaming Moving Picture Experts Group (Mpeg) Through Peer to Peer Networks - Desita Ria Yusian TB (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2018)
Multimedia streaming is a technology that can transmit digital audio and video files in real time on a computer network. It is most influential in the process include video streaming bandwidth, synchronization and delay, as well as Interoprability. In the streaming trials conducted found differences between upload video files with the extension * .avi file from the server and then downloaded by the client. Differences in get, among others: 1.274KB/sec, 1.58KB/sec and 2.07KB/sec for each MPEG-1, MPEG-2, and MPEG-4.Keywords : Streaming multimedia, MPEG, peer-to-peer, VLC